Kedudukan Hukum Organisasi Kemasyarakatan dalam Perspektif Siyasah - Haidar Adam (Bahasa Indonesia, 2024)
The legal status of community organizations (ormas) is a crucial component of Indonesia's legal system, representing the role of civil society. Ormas serve not only as a platform for public participation but also as a social watchdog for government policies. From a juridical perspective, the existence of ormas is regulated under Law No. 16 of 2017, which guarantees freedom of association while imposing limits to prevent abuse of authority. Furthermore, the legal status of ormas registered as legal entities ensures certainty and protection for their activities. However, regulations on the dissolution of ormas pose challenges, particularly in ensuring the principles of justice, transparency, and human rights protection. Therefore, balanced oversight is essential to maintain the supportive role of ormas in democracy while aligning with constitutional values.